Immune tolerance induction to factor VIII - Herzog, Roland W. (Henry Stewart Talks, 2020)
Replacement therapy for patients with hemophilia utilizes Factor VIII, Replacement therapy is rejected by the immune system, Exploring immune tolerance to Factor VIII, Engineering regulatory T cells therapy, Various small molecular and monoclonal antibody drugs, Hepatic AAV gene therapy, Plant-based oral tolerance